Dynamic Detection Based on Planar Array Capacitance for Adhesive Defects of Thermal Protection Structure. Issue 1 (1st February 2023) - Sun, Yurong; Zhang, Yuyan; Wen, Yintang
Abstract: The defect detection of thermal protective structures is of great significance in ensuring the safe flight of aircraft. In this paper, a dynamic measurement method based on the planar capacitance sensing principle is proposed to solve the problem of detecting defects in the adhesive layer of large-area thermal protection structures. This paper analyses the principle of capacitive sensing and establishes a planar array capacitive dynamic detection system. The dielectric distribution of the structural components to be measured is obtained at different locations by moving the array of electrode sensors regularly. To obtain the dielectric distribution information of the complete structure, the dielectric distribution at adjacent locations is spliced and fused. To achieve the precise location of the overlapping areas in the image to be fused, an image alignment method based on coordinates is adopted. The experimental results show that our proposed method can detect defects in the adhesive layer of large-area thermal protection structures and achieve complete visualization of the adhesive layer.